An Innovative Method for Digital Media Education Based on Mobile Internet Technology - Ma, Hongxia; Li, Jing (International Journal of Emerging Technologies in Learning (iJET), 2021)
The progress and popularization of the mobile Internet herald the age of Internet plus education. With the deepening of education reform, China raises new requirements on the key competencies of students. Focusing on the cultivation of these competencies, this paper develops an innovative method for digital media education based on mobile Internet technology. After surveying the current learning state of students majoring in digital media, the authors proposed a blended teaching model with digital media based on mobile Internet technology. There are four parts of the model, namely, frontend analysis, online autonomous learning, offline teaching, and after-class online evaluation. The design of each part was described in details. Then, the proposed model was applied to the Poster Design course of digital media major. Comparative analysis shows that the model promotes students’ learning efficiency, and their key competencies, and receives high recognition from the students. This research provides new impetus to the innovation of digital media education based on mobile Internet technology.